2009
DOI: 10.1016/j.jtcvs.2008.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of multivalvular endocarditis: Twenty-one–year single center experience

Abstract: In our institution, multivalvular endocarditis was diagnosed by transthoracic echocardiography in only half of the patients. Intraoperative transesophageal echocardiography provided a more effective means to identify this disease. Radical resection of all infected tissues for patients with multivalvular endocarditis and additional intraoperative interventions, depending on the intraoperative pathologic condition, produced satisfactory in-hospital and long-term results, similar to those in patients with a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Streptococcus viridans was the most common microorganism of the multiple valve group (70.6%) in our population, which was consistent with the previous reports of surgical experience [5,10,11]. Surprisingly, the most common etiologic microorganism was Staphyloccocus aureus in the other report of surgical experience of multiple valve IE [9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Streptococcus viridans was the most common microorganism of the multiple valve group (70.6%) in our population, which was consistent with the previous reports of surgical experience [5,10,11]. Surprisingly, the most common etiologic microorganism was Staphyloccocus aureus in the other report of surgical experience of multiple valve IE [9].…”
Section: Discussionsupporting
confidence: 91%
“…Prosthetic valve endocarditis differs from native valve endocarditis in that it has a more difficult diagnosis and surgical strategy, and worse prognosis [12]. Only a few studies have specifically focused on surgical therapy for multiple native valve IE [4,10,11]. We reviewed the surgical outcomes of native valve IE, and compared single valve surgery with multiple valve surgery during the past 15 years in Sejong General Hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have evaluated that the freedom from IE recurrence after valve surgery was between 80% and 90% at 5 years, although the predictors of IE recurrence were not analyzed. 18,24,25 Renzulli and colleagues 26 reported that not DM, but prosthetic valve endocarditis, positive valve culture, and persistent fever at seventh postoperative day were the predictors of IE recurrence. In the present study, the presence of DM was the only independent predictor of IE recurrence, and approximately 10% of patients with DM developed IE recurrence during the first year.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral IE usually occurs in patients with intracardiac devices [8] or congenital heart disease [9], or intravenous drug users [10]. However, the patient did not have these backgrounds.…”
Section: Discussionmentioning
confidence: 99%